Impact of SnF2 Addition on AC Susceptibility and Electrical Properties of Bi1.6Pb0.4Sr2CaCu2O8 Superconductor - Yusof N.M.; Bakar I.P.A.; Suib N.R.M.; Mujaini M.; Shukor R.A.; Jusoh M.M.; Abdullah H.; Azman N.J. (Malaysian Institute of Chemistry, 2025)
The effect of SnF2 addition on the superconducting properties of Bi1.6Pb0.4Sr2CaCu2O8 (SnF2)x with x = 0-1.0 wt. % is reported. All samples were prepared by the solid-state reaction route. The powder X-ray diffraction (XRD) patterns revealed a single Bi-2212 phase for all samples. Scanning electron micrographs showed plate-like structure which increased in grain sizes with SnF2 addition. The temperature-dependent resistance measurement showed the highest Tc onset (91 K) was for x = 0.5 wt. % sample which belongs to the Bi-2212 phase. The susceptibility transition temperature, Tc?? for all samples was between 72-81 K. The lower peak temperature at the imaginary part of susceptibility ??, Tp2 was suppressed with SnF2 addition indicating the weakening of intergranular coupling and flux pinning force. This work showed that SnF2 addition not only resulted in a single Bi-2212 phase but also enhanced the transition temperature and grains growth of Bi1.6Pb0.4Sr2CaCu2O8. The role of internal lattice strain in improving the transition temperature of Bi1.6Pb0.4Sr2CaCu2O8 was also discussed. ? 2024 Malaysian Institute of Chemistry. All rights reserved.